Islam and the State: The Evolution of Sharia Banking Regulation in Indonesia - Hidayah, Nur; Haryatih, Haryatih; Kamilah, Rihadatul Aisy (Fakultas Syariah UINSI Samarinda, 2024)
The interplay of social, economic, and political dynamics influences the legal development of Sharia banking regulations. This study aims to analyze the evolution of Sharia banking regulations in Indonesia from their inception to the most recent developments. Using a juridical-legal approach, the research identifies five key phases in the development of Sharia banking regulations in Indonesia: initial, introduction, recognition, purification, and relaxation phases. Such regulatory changes have resulted from the negotiations among various stakeholders to reconcile the ideals of Sharia finance with the pragmatic needs of the banking industry, as well as the interest in strengthening the national financial system. Such legal development of Sharia banking regulations in Indonesia reflects the adaptability of Islamic law, enabling Sharia finance to evolve in response to societal changes and contextual dynamics while remaining grounded in the ethical principles of the Islamic moral economy.